YOUTH SPIRITUALITY IN THE MODERN INFORMATION SPACE: DESTRUCTIVE THREATS AND NATIONAL PROTECTION MECHANISMS - Madraximov Vaisbay Baxtiyarovich (Journals Park Publishing, 2025)
This article analyzes the fact that modern media have a profound impact on the spiritual world of young people, the media is becoming an "ideological weapon", the Internet is the main channel for the dissemination of destructive ideas (3 billion users), the capture of youth consciousness is a new way to subjugate the state, and information attacks, fake information and cyberattacks violate national values. As a solution: 1) Cyberimmunity programs, 2) Parental education, 3) Promoting national values in the neighborhood. Cyberspace is proposed as a strategic space equal to land, water, and air.
Keywords: Ideological weapon, destructive ideologies, information attacks, spiritual gap, cyberimmunity, national identity, media education.